E. adenophorum induces Cell Cycle Arrest and Apoptosis of Splenocytes through the Mitochondrial Pathway and Caspase Activation in Saanen Goats - He, Yajun (Nature Publishing Group, 2015)
The precise cytotoxicity of E. Adenophorum in relation to the cell cycle and apoptosis of splenocytes in Saanen goats remains unclear. In the present study, 16 Saanen goats were randomly divided into four groups, which were fed on 0%, 40%, 60% and 80% E. adenophorum diets. The results of TUNEL, DAPI and AO/EB staining, flow cytometry analysis and DNA fragmentation assays showed that E. adenophorum induced typical apoptotic features in splenocytes, suppressed splenocyte viability, and caused cell cycle arrest in a dose-dependent manner. However, westernblot, ELISA, qRT-PCR and caspase activity analyses showed that E. adenophoruminhibited Bcl-2 expression, promoted Bax translocation to the mitochondria, triggered the release of Cytc from the mitochondria into the cytosol, and activated caspase-9 and -3 and the subsequent cleavage of PARP. Moreover, in E. adenophorum-induced apoptosis, the protein levels of Fas, Bid, FasL and caspase-8 showed no significant changes. E. adenophorum treatment induced the collapse of ΔΨm. Moreover, these data suggested that E. adenophorum induces splenocyte apoptosis via the activation of the mitochondrial apoptosis pathway in splenocytes. These findings provide new insights into the mechanisms underlying the effects of E. adenophorum cytotoxicity on splenocytes.